Poverty And Nutritional Problems: A Global Perspective With Focus On Indonesia- A Bibliometric And Systematic Literature Review - Ayuni, Indah Muthia; Kasmita, Kasmita; Yuliana, Yuliana (Universitas Negeri Padang, 2025)
Poverty and malnutrition are interrelated global health challenges that require special attention from multiple disciplines. This study employs a Systematic Literature Review (SLR) combined with bibliometric analysis to identify research trends, publication patterns, and future research directions related to poverty and malnutrition. Research data were obtained from the Scopus database using the keywords “poverty OR socioeconomic OR low income AND malnutrition OR nutritional status OR stunting AND Indonesia” up to December 16, 2025, yielding an initial 7.878 documents that were subsequently screened down to 118 articles meeting the inclusion criteria. Bibliometric analysis was conducted using VOSviewer and Bibliometrix to analyze keyword networks, author collaborations, and publication trends, as well as to visualize the scientific landscape of the research field. The results indicate that research on poverty and malnutrition remains a highly significant topic in academic discourse, with an exponential increase in publications since 2019. Indonesia dominates this research field with 102 articles (86.4%), followed by Australia and the United States, each contributing 14 articles. The bibliometric analysis also identified core keywords such as “Indonesia,” “nutritional status,” “stunting,” “malnutrition,” and “poverty,” reflecting a predominant focus on child nutritional status and its socioeconomic determinants. These findings underscore the need for further research in other developing countries and for the design of sustainable, multisectoral interventions to address these interconnected challenges.